(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The monograph under review is relevant because retinoblastoma is the most common primary intraocular malignancy of childhood, with a prevalence of about 11 cases per 1 million children under 5 years of age, and occurring in 1 of 18,000-30,000 live births. An estimated 250-500 new cases of retinoblastoma occur in the United States yearly, and the disease has no significant predilection for gender or The monograph consists of 7 sections, 27 chapters dedicated to modern worldwide diagnosis, treatment and relapse. race (Marichelle Aventura Isidro, 2019). The monograph is of additional value since early diagnosis of retinoblastoma is essential for reducing morbidity and mortality. The majority of patients (90%) present before 5 years of age, with a median age at diagnosis of 18 months. achievements in retinoblastoma (RB): epidemiology, histopathology, classification, The personal supervision of the Pediatric Ophthalmology Department (Filatov Eye Institute, Odessa, Ukraine) under prof. Nadiia Bobrova guidance based on clinical material of 418 patients (552 eyes) with RB for more than a 30-year period. The modern RB imaging modes (ultrasound, FAG, SOCT, MRI) in RB differential diagnoses are presented. The first line conservative RB treatment – polychemotherapy (PCT), its complications and results are